PERUMUSAN STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN UMBI-UMBIAN LOKAL DI YOGYAKARTA [Design of Regional Government Strategy in Development the Local Tube Crops in Yogyakarta] - Purwadi, Didik (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2018)
Local tuber crops are increasingly forced to exist, both because of the absence of market needs and the decrease of cultivation. In line with the carbohydrate diversification program, it is necessary to reformulate the current government policies related to tubers. The purpose of this study was to identify strengths, weaknesses, opportunities, and threats in the development of tubers, and formulate development strategies in the Special Region of Yogyakarta. This study used a qualitative descriptive approach, with SWOT techniques and disaggregation strategies. Based on this study, the government must improve coordination between agencies or institutions related to tubers, develop subsidy schemes to improve farmers' competitiveness through a more equitable system, and empower farmer groups, as well as develop cooperation in distribution networks and tubers information.